Análisis de la equidad de género en los emprendimientos, caso Calceta, Junín y Tosagua - Gonzabay Freire, Jossenka Katherine (2025)
This research delves into the issue of deeply rooted gender stereotypes in Ecuadorian society and their impact on entrepreneurship in the cantons of Calceta, Junín, and Tosagua in the province of Manabí. Emphasizing entrepreneurship as an economic driver and highlighting gender disparities in employment rates, the study's main objective is to assess gender equity within these entrepreneurial ventures. The methodology is grounded in inductive, deductive, and analytical-synthetic approaches, supported by the analysis of indicators from Sustainable Development Goal (SDG) 5. Through this lens, both progress and persistent challenges are revealed, underscoring the complexity of achieving gender equality. A review of the legal framework shows Ecuador’s formal commitments to gender equity, yet stresses the urgent need for effective implementation. The conclusions highlight the country’s legal commitment to promoting gender equality in entrepreneurship, while underscoring the importance of social awareness and political will in driving real change. The study calls for strong political leadership, investment, and comprehensive reforms to overcome systemic barriers and build a more inclusive society. It also stresses the need to close existing gaps in local political representation and leadership roles, proposing concrete actions and the ratification of the Optional Protocol as key steps toward eliminating gender discrimination